Integrated Deterrence in Practice: The 2022 United States National Defense Strategy Towards the Russia-Ukraine War - Masitoh, Yuniar Tri; Perwita, Anak Agung Banyu; Rudy, Elphis (International Journal of Humanities, Education, and Social Sciences, 2025)
This paper analyzes the implementation of integrated deterrence by the United States, as articulated in the 2022 National Defense Strategy (NDS), in response to the Russia–Ukraine War. The central issue examined is how a strategy originally tailored to counter China was adapted to address Russia’s invasion of Ukraine. Integrated deterrence seeks to align military and non-military instruments across domains and in coordination with allies, yet its real-world application presents complex challenges. The objective of this study is to assess how integrated deterrence was operationalized, evaluate its effectiveness, and identify key lessons for future defense planning. Employing a qualitative case study approach grounded in the framework of neoclassical realism, the research draws on official policy documents, expert commentary, and academic analyses. The findings reveal that the United States effectively leveraged integrated deterrence to support Ukraine without direct military engagement, utilizing a combination of economic sanctions, cyber defense, intelligence sharing, and diplomatic coordination. While the strategy did not prevent the initial invasion, it contributed to denying Russia a swift victory and reinforced NATO cohesion. The study concludes that integrated deterrence offers strategic flexibility and strengthens coalition responses in an increasingly complex global security landscape. However, its success is contingent upon domestic political consensus, sustained resource commitments, and a nuanced understanding of adversary behavior. The research underscores the need to adapt integrated deterrence for varying threat environments, particularly in the Indo-Pacific region, where escalation dynamics and regional contexts differ significantly.